Study on mechanism of influence of low temperature freeze-thaw cycle on spontaneous combustion characteristics of coal gangue - Xun Zhang; Ning Ma; Bing Lu; Fengwei Dai; Ge Huang; Huimin Liang; Chen Yu (Case Studies in Thermal Engineering)
In order to investigate the influence of the number of freeze-thaw cycles (freeze-thaw) on the spontaneous combustion characteristics of coal gangue, this study simulated the alpine environment and examined the spontaneous combustion characteristics of coal gangue after undergoing multiple freeze-thaw cycles. The evolution of the macro-oxidative exothermic properties and microstructural characteristics of the gangue during the freeze-thaw cycles were analyzed by X-ray diffraction (XRD), low-temperature N2 adsorption (LTNA), programmed temperature-expanded oxidation (PTO), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR), and other experimental means. The results showed that the freeze-thaw cycle significantly promoted the spontaneous combustion effect of gangue, and the effect showed an increasing and then decreasing trend with the increase in the number of cycles, and reached the maximum in the fourth freeze-thaw cycle. The mineral composition of the gangue changed significantly during the freeze-thaw cycle, and the pyrite content decreased by 5.5 %. The apparent activation energy decreased to the lowest in the fourth freeze-thaw cycle, which was only 0.79 times of the untreated sample, while the exothermic amount also reached the peak, which was about 1.71 times of the untreated sample. In addition, -CH3, C=O, and -OH contents firstly increased and then decreased with the number of freeze-thaw cycles, and all of them reached a great value at the fourth freeze-thaw cycle. Further analysis showed that the freeze-thaw cycle caused nonlinear changes in the spontaneous combustion effect of coal gangue by regulating the mineral composition, pore structure, and FeS2 reaction of the gangue, which was shown to be enhanced at the beginning of the cycle and weakened with the increase in the number of cycles.